THE EVOLUTION OF LEADERSHIP IN THE MODERN PROFESSIONAL LANDSCAPE: SHIFTING PARADIGMS AND THEIR IMPACTS - Jayanagara, Oscar (Feedforward: Journal of Human Resource, 2024)
Leadership plays a pivotal role in guiding and shaping organizations and teams. In the modern professional world, leaders have undergone a transformation, influenced by various factors such as technological advancements, shifting societal expectations, and the dynamics of globalization. This study presents a comprehensive exploration of the multifaceted nature of leadership evolution in the workplace, drawing on data from qualitative research, interviews, and scholarly literature reviews. The findings highlight the shift from hierarchical to collaborative leadership, emphasizing increased interaction, teamwork, and innovation. Furthermore, the significance of communication and collaboration skills in leaders is underscored, with effective communication linked to enhanced team performance and collaboration skills as a key driver of organizational success. In addition, innovation and creativity are identified as critical components of effective leadership, fostering enhanced productivity and competitive advantage. These changes in leadership systems have far-reaching implications, affecting productivity, job satisfaction, and innovation in the workplace. The study underscores the need for leaders to adapt to this evolving landscape and integrate these essential leadership skills, ultimately contributing to effective leadership in the contemporary professional world. This research offers valuable insights into the dynamic nature of leadership in the evolving professional context.